Strengthening Digital Data-Based Asset Management Systems to Support School Accountability - Luthfi Firdaus; Fajrin Satria Dwi Kesumah; Salsabila; Reka Aldilana Ramadhan (Journal Social Science And Technology For Community Service, 2026)
This community service activity aims to strengthen the asset management system at YP Unila High School through the implementation of a simple yet effective digital-based database. Initial observations identified key issues such as scattered asset records, data inconsistencies, and minimal handover documentation, which could potentially reduce the accountability and efficiency of school governance. Interventions included designing a Microsoft Excel-based database template, providing technical training, and assisting with implementation through the initial data entry stage. Pre-post test results for 15 participants (staff) showed an average score increase of 17 points, indicating the training's effectiveness in enhancing human resource capacity. The evaluation also revealed a reduction in asset naming variations, increased inventory code consistency, and the emergence of a data-driven work culture. Further discussion, referring to academic literature, confirmed that asset digitization not only simplifies administrative processes but also strengthens the principles of good governance through transparency and accountability. This program can be replicated in other schools using a phased approach and developed into a web-based system for more comprehensive and sustainable data integration.